Intraspecific responses to distress calls of the pipistrelle bat,Pipistrellus pipistrellus - Russ, J.M; Racey, P.A; Jones, G (Zenodo, 1998)
(Uploaded by Plazi for the Bat Literature Project) Responses of the vespertilionid bat Pipistrellus pipistrellus to five recently caught conspecifics confined to a wire-mesh cage, at distances of 50 and 5 m from their roosts, were recorded on 12 separate evenings at three roosts during pregnancy and lactation. When bats were confined 50 m from their roost, an almost 20-fold increase in the number of bats that passed across an open site around the cage was recorded and the strength of response (number of bat passes) increased with time. When the bats were 5 m from the roost there was an 80-fold increase in bat activity above the cage. Playbacks of recorded distress calls produced by single hand-held bats resulted in a more than three-fold increase in bat passes, but the response waned rapidly. The distress calls of recently caught P. pipistrellus were generally similar to those of individuals from the same colony held for longer in captivity, and differences in distress calls between two of the three colonies studied probably reflect differences in the physiological states of recorded bats, rather than the existence of colony-specific vocalizations. Distress calls probably function in attracting conspecifics which perform mobbing behaviour as an anti-predator response.